2001
DOI: 10.1080/028418501127346224
|View full text |Cite
|
Sign up to set email alerts
|

CTA in patients with acute subarachnoid haemorrhage: A comparative study with selective, digital angiography and blinded, independent review

Abstract: CTA in SAH is of great value in demonstrating vascular anatomy and the exact size of an aneurysm. However, IA-DSA is still needed for diagnostic evaluation in aneurysms smaller than 5 mm in diameter, especially in those located near bony structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
2
16
0
2
Order By: Relevance
“…These studies reported variable sensitivity and specificity values ranging from 67% to 100% and 86% to 100%, respectively 8 18–21. One study19 compared CTA with DSA in detecting aneurysms in SAH patients and reported a sensitivity of 91% and specificity of 95% after 1 year's experience of using CTA. In this report, 13 out of 144 aneurysms were missed by CTA.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported variable sensitivity and specificity values ranging from 67% to 100% and 86% to 100%, respectively 8 18–21. One study19 compared CTA with DSA in detecting aneurysms in SAH patients and reported a sensitivity of 91% and specificity of 95% after 1 year's experience of using CTA. In this report, 13 out of 144 aneurysms were missed by CTA.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these cases occurred early in the study (the case with the 4 mm aneurysm located at RMCA was our first patient) when our experience was sub par. Lack of experience has been reported as a cause of misdiagnosis by other studies as well (2,8,18,24,32). Pedersen et al (32) reported an increase in the sensitivity of CTA from 88% to 94% after 1 year's experience.…”
Section: Discussionmentioning
confidence: 88%
“…Lack of experience has been reported as a cause of misdiagnosis by other studies as well (2,8,18,24,32). Pedersen et al (32) reported an increase in the sensitivity of CTA from 88% to 94% after 1 year's experience. Westerlaan et al (1) recommends that if a cranial CTA study is reported as normal despite a strong clinical suspicion of a ruptured aneurysm, a second radiologist should review the study before scheduling a repeat angiography.…”
Section: Discussionmentioning
confidence: 88%
“…The learning curve of experience has been described for CT angiography. 33 There is no trend toward higher diagnostic performance in smaller studies, so the funnel plot gives no indication for publication bias. 34 The implications of the results of this meta-analysis for the position of MRA in clinical practice need to be discussed.…”
Section: Discussionmentioning
confidence: 99%